2023
DOI: 10.2147/bctt.s408743
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Real-World HER2-Low Data in Early-Stage Triple-Negative Breast Cancer: Insights and Implications

Jesse Lopes da Silva,
Giselle de Souza Carvalho,
Lucas Zanetti de Albuquerque
et al.

Abstract: This study aimed to compare the clinical behavior, clinicopathological and sociodemographic characteristics of patients with early-stage triple-negative breast cancer (TNBC) who belong to the HER2-low and HER2-zero subgroups. Patients and Methods: This study involved a thorough search in the internal database of a single Brazilian institution to identify women with TNBC who underwent neoadjuvant chemotherapy (NACT) followed by curative surgery within the period from January 2010 to December 2014. HER2 analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
(40 reference statements)
0
1
0
1
Order By: Relevance
“…The molecular classification has not changed and HER2 low cannot be considered a molecular subtype, but it is important to recognize these patients since in the DESTINY-Breast04 clinical trial, trastuzumab deruxtecan (T-DXd) demonstrated that even fewer HER2 receptors on cancer cells may be sufficient for clinical benefit 20 , 21 . Evaluation of this subgroup, especially in those triple-negative patients, is vital as it will allow targeted therapies, new clinical trials and the development of more accurate techniques to assess HER2 status 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular classification has not changed and HER2 low cannot be considered a molecular subtype, but it is important to recognize these patients since in the DESTINY-Breast04 clinical trial, trastuzumab deruxtecan (T-DXd) demonstrated that even fewer HER2 receptors on cancer cells may be sufficient for clinical benefit 20 , 21 . Evaluation of this subgroup, especially in those triple-negative patients, is vital as it will allow targeted therapies, new clinical trials and the development of more accurate techniques to assess HER2 status 22 .…”
Section: Discussionmentioning
confidence: 99%
“…La clasificación molecular no ha cambiado y HER2 low no puede ser considerado un subtipo molecular, pero es importante reconocer a estos pacientes dado que en el ensayo clínico DESTINY-Breast04, trastuzumab deruxtecan (T-DXd) demostró que incluso menos receptores HER2 en las células cancerosas pueden ser suficientes para obtener beneficio clínico 20 , 21 . La evaluación de este subgrupo, en especial en aquellos pacientes triple negativo, es vital ya que permitirá terapias específicas, nuevos ensayos clínicos y el desarrollo de técnicas más precisas para evaluar el estado de HER2 ( 22 .…”
Section: Discussionunclassified